Strategi Keterlibatan Orang Tua dalam Pendidikan Anak di Era Digital - Yohanes Mandala; Andrian Wira Syahputra; Hendrik A E Lao (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Technological progress is inevitable. In today's digital era, technology has been completely assimilated into our daily lives. The lives of young children today have changed in several ways as a result of this. The digital era offers advantages and disadvantages. As the individuals closest to their children, parents must be able to use appropriate parenting techniques in the digital era so that their children are not affected by the negative impacts of technological advances. This post will discuss a number of digital-based early childhood education practices that parents can implement. It is hoped that parents can implement these strategies in order to reduce the negative impacts of using digital media.